: Desarrollo de guía práctica para el aprendizaje de la Segunda Ley de Newton utilizando el software Interactive Physics - Revelo Borja, Daniel Alejandro (2023)
As has been observed in various educational centers in Latin America, most of them have been teaching the chair of Physics in a continuous or orthodox way, which has shown that they have not fully engaged with the new methods, educational means and tools which are now available, partly as a reason for the disinterest and poor academic performance of the majority of students, denoting that, both teachers and students have not been involved in the use of software for the development of the teaching and learning process. What this proposal of developing a practical guide for learning physics explicitly with respect to Newton’s second law is that, students have Access to a tool that helps to better understand this subject as such, inducing each of them to use software for adaptation in their classes, focusing on modeling the problem through their simulation, thus enabling the participants to understand the phenomena that may occur; whereas it is not the same to show on a blackboard a graph or a schematic of the event, to which, each of them manipulate the possible surrounding factors that could arise in a problem. A survey was carried out with students and teachers to determine the degree of acceptance and interest of the guide, having a favorable result for its development, so the design of the research was proposed as an experimental and bibliographical type, having a descriptive level, considering that the results obtained in the survey were not reference for the development of the ecosystem of the guide.